The cost‐effectiveness of prophylaxis strategies for individuals with advanced HIV starting treatment in Africa. Issue 3 (27th March 2020) - Walker, Simon M; Cox, Edward; Revill, Paul; Musiime, Victor; Bwakura‐Dangarembizi, Mutsa; Mallewa, Jane; Cheruiyot, Priscilla; Maitland, Kathryn; Ford, Nathan; Gibb, Diana M; Walker, A Sarah; Soares, Marta; et al.
Abstract: Introduction: Many HIV‐positive individuals in Africa have advanced disease when initiating antiretroviral therapy (ART) so have high risks of opportunistic infections and death. The REALITY trial found that an enhanced‐prophylaxis package including fluconazole reduced mortality by 27% in individuals starting ART with CD4 <100 cells/mm 3 . We investigated the cost‐effectiveness of this enhanced‐prophylaxis package versus other strategies, including using cryptococcal antigen (CrAg) testing, in individuals with CD4 <200 cells/mm 3 or <100 cells/mm 3 at ART initiation and all individuals regardless of CD4 count. Methods: The REALITY trial enrolled from June 2013 to April 2015. A decision‐analytic model was developed to estimate the cost‐effectiveness of six management strategies in individuals initiating ART in the REALITY trial countries. Strategies included standard‐prophylaxis, enhanced‐prophylaxis, standard‐prophylaxis with fluconazole; and three CrAg testing strategies, the first stratifying individuals to enhanced‐prophylaxis (CrAg‐positive) or standard‐prophylaxis (CrAg‐negative), the second to enhanced‐prophylaxis (CrAg‐positive) or enhanced‐prophylaxis without fluconazole (CrAg‐negative) and the third to standard‐prophylaxis with fluconazole (CrAg‐positive) or without fluconazole (CrAg‐negative). The model estimated costs, life‐years and quality‐adjusted life‐years (QALY) over 48 weeks using three competing mortality risks: cryptococcal meningitis; tuberculosis, serious bacterial infection or other known cause; and unknown cause. Results: Enhanced‐prophylaxis was cost‐effective at cost‐effectiveness thresholds of US$300 and US$500 per QALY with an incremental cost‐effectiveness ratio (ICER) of US$157 per QALY in the CD4 <200 cells/mm 3 population providing enhanced‐prophylaxis components are sourced at lowest available prices. The ICER reduced in more severely immunosuppressed individuals (US$113 per QALY in the CD4 <100 cells/mm 3 population) and increased in all individuals regardless of CD4 count (US$722 per QALY). Results were sensitive to prices of the enhanced‐prophylaxis components. Enhanced‐prophylaxis was more effective and less costly than all CrAg testing strategies as enhanced‐prophylaxis still conveyed health gains in CrAg‐negative patients and savings from targeting prophylaxis based on CrAg status did not compensate for costs of CrAg testing. CrAg testing strategies did not become cost‐effective unless the price of CrAg testing fell below US$2.30. Conclusions: The REALITY enhanced‐prophylaxis package in individuals with advanced HIV starting ART reduces morbidity and mortality, is practical to administer and is cost‐effective. Efforts should continue to ensure that components are accessed at lowest available prices.